2016
DOI: 10.1007/s10664-016-9482-0
|View full text |Cite
|
Sign up to set email alerts
|

An initial analysis of software engineers’ attitudes towards organizational change

Abstract: Employees' attitudes towards organizational change are a critical determinant in the change process. Researchers have therefore tried to determine what underlying concepts that affect them. These extensive efforts have resulted in the identification of several antecedents. However, no studies have been conducted in a software engineering context and the research has provided little information on the relative impact and importance of the identified concepts. In this study, we have combined results from previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…For example, a researcher wants to study the effects of physical punishment in schools in the 20th century, is a narrative research [Grbich, 2007]. In narrative research observations, diaries, letters, interviews, artifacts, and photographs collect data [Lenberg et al, 2017].…”
Section: Narrative Researchmentioning
confidence: 99%
“…For example, a researcher wants to study the effects of physical punishment in schools in the 20th century, is a narrative research [Grbich, 2007]. In narrative research observations, diaries, letters, interviews, artifacts, and photographs collect data [Lenberg et al, 2017].…”
Section: Narrative Researchmentioning
confidence: 99%
“…A potential direction for decision model research should therefore be to look further into the core human factors that affect the decision-maker and their final asset selection. Such research is also warranted by related software engineering research into, for instance, how human factors affect cost estimation (Magazinius et al 2012), process improvement (Lenberg et al 2017), and behavioral software engineering (Lenberg et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Openness towards organizational change also depends on both individual variables (e.g., self-esteem, optimism, perceived control) and context-specific variables (e.g., information, participation, change selfefficacy, social support, personal impact). Furthermore, Lenberg et al [7] reported that workers' feelings of participation in the change process, the knowledge about the intended changes outcomes, and their understating of the need for organizational change together impact on their attitudes towards said change. Occupational stressors, particularly poor work relationships, were negatively related to the attitudes towards change.…”
Section: Openness Toward Changementioning
confidence: 99%
“…Changes in work contexts, negative perceptions of key members, the perceived lack of reciprocation of trust and respect, and negative perceptions of leadership/management contribute to the decline in organizational commitment [6]. As individuals' attitudes towards change play a fundamental role in the change process [7], conceptual work on measuring attitudes toward change appropriately continues to compel interest [8,9]. One such employee attitude, openness to change, can be defined as positive affect and support for change and its consequences [10].…”
Section: Introductionmentioning
confidence: 99%